IDENTIFICATION, ISOLATION, PURIFICATION, GRAM STAINING, AND BIOCHEMICHAL TESTING PROCESSES OF AQUATIC BACTERIA FROM DIFERENT SOURCES - Pardede, Maria Agustina; Fasya, Arif Habib; Kumalaningrum, Dwi Retna; Ulkhaq, Mohammad Faizal; Kenconojati, Hapsari; Ambarwati, Dewi; Maulana, Muhammad Hilmy (Politeknik Kelautan dan Perikanan Dumai, 2024)
Abstract